Introduction to governmental and not-for-profit accounting - Ives, Martin; Patton, Suesan R.; Patton, Terry K. (Pearson, 2013)
For use in Governmental Accounting, Not-for-Profit Accounting and Public Administration courses. Ives presents a comprehensive, practical, clearly written, and updated approach to governmental and not-for-profit financial accounting